2012
DOI: 10.1182/blood-2012-03-416156
|View full text |Cite|
|
Sign up to set email alerts
|

Neutrophil extracellular traps mediate transfer of cytoplasmic neutrophil antigens to myeloid dendritic cells toward ANCA induction and associated autoimmunity

Abstract: Antineutrophil cytoplasmic antibodies (ANCAs) target proteins normally retained within neutrophils, indicating that cell death is involved in the autoimmunity process. Still, ANCA pathogenesis remains obscure. ANCAs activate neutrophils inducing their respiratory burst and a peculiar form of cell death, named NETosis, characterized by formation of neutrophil extracellular traps (NETs), decondensed chromatin threads decorated with cytoplasmic proteins endorsed with antimicrobial activity. NETs have been consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
314
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(326 citation statements)
references
References 45 publications
4
314
0
5
Order By: Relevance
“…The activation of DCs by NETs appears to play an important role in the pathogenesis of some autoimmune diseases such as psoriasis (Lande et al, 2007), systemic lupus erythematosus (SLE) (Barrat et al, 2005;Garcia-Romo et al, 2011;Lande et al, 2011;Means et al, 2005) small vessel vasculitis (Sangaletti et al, 2012) and type I diabetes (Diana et al, 2013). NETsactivated pDCs produce large amounts of interferon that can lead to the maturation of myeloid DCs (mDCs) and exert an effect on T cell function.…”
Section: -Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of DCs by NETs appears to play an important role in the pathogenesis of some autoimmune diseases such as psoriasis (Lande et al, 2007), systemic lupus erythematosus (SLE) (Barrat et al, 2005;Garcia-Romo et al, 2011;Lande et al, 2011;Means et al, 2005) small vessel vasculitis (Sangaletti et al, 2012) and type I diabetes (Diana et al, 2013). NETsactivated pDCs produce large amounts of interferon that can lead to the maturation of myeloid DCs (mDCs) and exert an effect on T cell function.…”
Section: -Introductionmentioning
confidence: 99%
“…In SLE, pathogenic auto-antibodies have been associated with abnormal clearing of NETs and NETosis that results in abnormally high production and/or low degradation of NETs, which then leads to tissue damage and facilitated generation of large quantities of auto-antibodies creating a vicious cycle (Knight and Kaplan, 2012). In small vessel vasculitis, NETs can favor neutropil proteins uploading into mDCs and the induction of anti-neutrophil cytoplasmic antibodies (ANCAs) (Sangaletti et al, 2012). Recently, we demonstrated that NETs are also able to directly prime T cells by reducing their activation threshold, which represents a novel link between innate and adaptive immune responses .…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the functional link between NETosis and CD5 + B-cell proliferation was independent of the Fas or Sparc genotype; neutrophils from wild-type (WT) spleens were able to stimulate CD5 + B-cell proliferation following induction of NETosis with PMA (ref. 29 ; Fig. 4B ).…”
Section: Nets Stimulate Cd5 + B-cell Proliferation Via Nf-kbmentioning
confidence: 99%
“…29 ). In addition, NETosis requires myeloperoxidase (MPO) expression ( 30 ), which was increased in the spleens of lpr/lpr/ Sparc −/− mice with NET-like extracellular structures ( Fig.…”
Section: Research Articlementioning
confidence: 99%